The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1126/science.aaf4914
|View full text |Cite
|
Sign up to set email alerts
|

Origin and hysteresis of lithium compositional spatiodynamics within battery primary particles

Abstract: Abstract:The kinetics and uniformity of ion insertion reactions at the solid/liquid interface govern the rate capability and lifetime, respectively, of electrochemical devices such as Li-ion batteries.We develop an operando X-ray microscopy platform that maps the dynamics of the Li composition and insertion rate in LiXFePO4, and show that nanoscale spatial variations in rate and in composition control the lithiation pathway at the sub-particle length scale. Specifically, spatial variations in the insertion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
504
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(550 citation statements)
references
References 46 publications
29
504
0
1
Order By: Relevance
“…5,32,53 Very recently, the physical picture of the mesoscopic elementary units in our model has been confirmed by high-resolution scanning transmission X-ray microscopy (STXM) observation of a very dilute LFP electrode. 54 This showed that stationary boundaries (as opposed to moving phase boundaries in conventional views of phase transformation) divide micron-sized particles into many single-phase solidsolution domains which are lithiating/delithiating to settle into either Li-rich or Li-poor phases at different rates and independently of one another (see movie S2 in Ref. 54).…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…5,32,53 Very recently, the physical picture of the mesoscopic elementary units in our model has been confirmed by high-resolution scanning transmission X-ray microscopy (STXM) observation of a very dilute LFP electrode. 54 This showed that stationary boundaries (as opposed to moving phase boundaries in conventional views of phase transformation) divide micron-sized particles into many single-phase solidsolution domains which are lithiating/delithiating to settle into either Li-rich or Li-poor phases at different rates and independently of one another (see movie S2 in Ref. 54).…”
Section: Model Developmentmentioning
confidence: 99%
“…54 This showed that stationary boundaries (as opposed to moving phase boundaries in conventional views of phase transformation) divide micron-sized particles into many single-phase solidsolution domains which are lithiating/delithiating to settle into either Li-rich or Li-poor phases at different rates and independently of one another (see movie S2 in Ref. 54). It has also been observed that the domains that lithiate first also delithiate first and those that lithiate last also delithiate last, confirming that such a meso-scale phase distribution within each particle is not related to nucleation and growth or spinodal decomposition mechanisms as proposed in other models.…”
Section: Model Developmentmentioning
confidence: 99%
“…Applying advanced manufacturing principles such as ink-jets could enable tailor-made thin structures reducing charge transfer losses and raise the efficiency of electrochemical devices. Advanced microscopy and characterization such as 3D tomography and nanoscale visualization [5] accompanied with interdisciplinary research (e.g., molecular dynamics simulations and machine learning for material science) could in turn broaden our understanding of the underlying phenomena for inefficiencies, heterogeneities, and aging. …”
Section: Way(s) Forwardmentioning
confidence: 99%
“…Gaining information on the structural and electronic changes occurring in the host material at the atomic scale is now crucial to improve the batteries performance. [17][18][19][20][21] For cathodes materials containing iron ions, 57 Fe Mössbauer spectroscopy allows to probe the redox state of the active iron(II/III) ions. 22 In the field of Li-ion batteries, 6 Li/ 7 Li NMR is also often used to investigate the Li + (de)intercalation processes during the charge and discharge.…”
mentioning
confidence: 99%